Comparison of compliance and response rate of radiotherapy alone vs. chemo radiotherapy in stage IIIB carcinoma cervix patients having obstructive uropathy - Rathore, Narendra; Gupta, Sunnia (International Journal of Research in Medical Sciences, 2017)
Background: Carcinoma cervix is the second most common malignancy among females of India (1). The low incidence rate in developed countries is because of well-developed screening programs and awareness among women. But in developing countries like India, because of lack of health awareness and lack of proper screening facilities, patients usually present in advanced stages. They also have a lot of associated co-morbidities like obstructive uropathy with or without deranged RFT, anaemia, poor nutrition, tuberculosis, diabetes, hypertension, multiple genital infections etc. The standard treatment of advanced carcinoma cervix is radiotherapy with weekly cisplatin as radio-sensitizer but it has been observed that a lot of patients are not able to tolerate toxic side effects of concurrent chemo radiotherapy. Methods: We have chosen only one co-morbid condition i.e. obstructive uropathy with or without deranged RFT because of small sample size. So the aim of this study was to compare the compliance and response rate of concurrent chemo radiotherapy versus radiotherapy alone in patients of locally advanced carcinoma cervix having obstructive uropathy with or without deranged RFT. Results:Only 36% (n=9) patients in the RT+CT group received the complete planned five cycles of weekly cisplatin. Average number of cycles of cisplatin missed in the chemo-radiotherapy group was one (range 0-3). Compliance was better in the RT alone group. The average time in the RT alone group to complete radiotherapy was 57.72 days and in RT+CT group was 60.72 days. In the RT alone group the treatment time was prolonged by an average of 1.72 days (range 3-6) while in the CT+RT group it was prolonged by 4.72 days (range 2-14). Conclusions:It is hereby concluded that radiotherapy alone for locally advanced squamous cell cervical carcinoma patients having associated co morbid conditions like deranged RFT had a better compliance then with the concurrent chemoradiotherapy regime.